Association of "green spot" and defoliation to Tenuipalpus heveae incidence and chemical control screening of Hevea brasiliensis diseases (Bioscience Journal, 2018)
According to IBGE data, in 2016, Brazil produced closer to 56 thousand hectares of rubber tree generating a total latex production of 315.62 tons in commercial areas and 1.6 thousand tons in native forests. But this growth in crop production is related to the raise of economic losses generated by foliar and bark (panel) diseases caused by Phytophthora spp, Colletotrichum sp., Lasiodiplodia spp., Colletotrichum sp., Ceratocystis fimbriata, Microcyclus ulei (leaf blight) and the leaf anomaly that we call here as "Green Spot". Also, due to the tapping method and the incisions or "injuries" made in this process, opportunistic pathogens can usually infect and end up growing in the bark. This type of infection that is also difficult to control with the adoption of chemical fungicides, can create additional damage to the rubber panels. Pathogens such as Oidium heveae, C. gloeosporioides (anthracnosis), Phomopsis sp. and Phytophthora spp. were identified in 42% of the areas of growers or farms. Treatments T3- (thiophanate-methyl (350 g.ha-1 active ingredient) and T4- (metiram (1.75 kg.ha-1 active ingredient)) were superior against rot diseases in the bark of rubber trees. It was described for the first time the anomaly of the green spot associated to the Tenuipalpus heveae mite in 65% of the samples and had its etiology confirmed by artificial inoculation in rubber tree seedlings. In the USP-ESALq, Dr. Kitajima, E., did not confirm the presence of rhabdovirus-like particles common to tenuipalpids that transmit the virus in coffee and citrus (nuclear and cytoplasmic viruses).